2022
DOI: 10.1155/2022/9393446
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Analysis of the Relationship between National Image Building and International Communication Ability from the Perspective of Ecology under the Media Environment

Abstract: With the gradual expansion of China’s political, economic, and military strength, the rapid rise of China has become a globally recognized fact. At present, although China’s international image as the world’s second largest economy, military power, and political power has been increasingly accepted by the global community, China’s image construction, as an important part of national soft power, is still facing many problems. This chapter focuses on defining the basic concepts of international publicity, China’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…In addition, some experts and scholars have discussed the ICCW from the aspects of the communication system [ 43 ], component construction [ 44 ], practice, and evaluation [ 45 ], and also studied the construction of government capacity of national communication from the aspects of current capacity construction [ 46 ], enhancement strategies [ 47 ], and construction paths [ 48 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, some experts and scholars have discussed the ICCW from the aspects of the communication system [ 43 ], component construction [ 44 ], practice, and evaluation [ 45 ], and also studied the construction of government capacity of national communication from the aspects of current capacity construction [ 46 ], enhancement strategies [ 47 ], and construction paths [ 48 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…It acts as a vital asset, enhancing the core competitiveness of a city. The process of broadcasting a city's image on a global scale is critical for its assimilation into the worldwide system and global discourse (Zhu and Zhang 2022). Additionally, it plays a key role in highlighting the competitiveness of a city brand and obtaining global resource allocation.…”
Section: Introductionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%